Effect of Shading and Mowing on the Growth of Indonesia’s Native Zoysia grass in Silty Clay Soil - Rahayu Rahayu; Mujiyo Mujiyo; Randy Ramadhan; Geun Mo Yang; Joon Soo Choi (Universitas Sebelas Maret, 2020)
In general, turfgrass grows well and forms high quality turf under full sun exposure. It is very difficult, however, to grow a warm season turfgrass under shaded condition. Zoysia grass is a popular warm season grass that commonly grow under full sun exposure condition. There are limited information regarding the growth response and turf quality of zoysia grass when grown under shaded condition. This study aims to observe the growth and quality of various zoysia grass local cultivars at different shading intensities and different mowing. This research was carried out using 10 zoysia grass cultivars planted in the rice fields’ vertisol clay with randomized complete block design. The shading used were control, shade-nets with 25% and 65% hole densities. Zoysia grass was fertilized using NPK; 4:1:3 and mowed three times. The results showed that plants without shade, 25% and 65% received on average solar irradiance of 25,141; 12,456 and 3,727 lux. The increase in shade level decreased the shoot fresh weight, dry weight, root dry weight and the plant height. Shading and frequent mowing effected the plant height. Mowing has more effect on plant height in 25% shading than in 65% shading. The increase in shading, in mowed grass showed increased plant height and decreased plant dry weight. Mowing three times can reduce plant height in all shades. The grasses under 25% shading resulted the highest plant dry weight; whereas and shading 65% resulted the lowest. Plant dry weight and uniformity of turf were affected by the cultivars.